Preparation and Evaluation of Fullerene Related Nano Carbon Phenobarbitone Conjugates for the Treatment of Epilepsy - Nanditha K; Hemalatha KP; Vijaykumar S; Mancy SP (The Bioscan, 2025)
This research focuses on developing a novel nanocarrier-based drug delivery system for epilepsy using polyethylene glycol (PEG)-functionalized multi-walled carbon nanotubes (MWCNTs) loaded with Phenobarbitone. The primary goal was to create a PEG–MWCNT–Phenobarbitone conjugate that enables sustained and controlled drug release, thereby enhancing therapeutic effectiveness and patient compliance. The MWCNTs were functionalized through a non-covalent method to improve their dispersion stability and drug-loading efficiency. Formulation optimization was conducted using a Design of Experiments (DOE) approach based on the Taguchi method to identify key parameters influencing performance. The conjugates were characterized using Fourier Transform Infrared Spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM). FT-IR confirmed successful attachment of Phenobarbitone to the functionalized MWCNTs, while SEM images revealed distinct morphological changes on the nanotube surface after drug loading. Particle size analysis showed values ranging from 95 to 950 nm, and a zeta potential of 23 mV indicated good stability of the formulation. The drug entrapment efficiency exceeded 85%, and the cumulative in vitro drug release reached approximately 89%, suggesting an effective sustained-release profile. The experimental design employed two factors at three levels, arranged in an L27 orthogonal array to ensure comprehensive evaluation of formulation variables. The optimized formulation demonstrated notable anticonvulsant activity in the Maximal Electroshock Seizure (MES) model, reflected by a significant reduction in the tonic limb extension phase. Statistical analysis validated the consistency and reliability of the experimental data. Overall, the PEG-functionalized MWCNT–Phenobarbitone conjugate showed excellent dispersion, stability, and prolonged release characteristics, indicating its strong potential as an advanced drug delivery system for epilepsy therapy. This study highlights the promising role of functionalized carbon nanotubes in improving the pharmacological performance of conventional antiepileptic drugs. KEYWORDS: Polyethylene glycol, Multi Walled Carbon Nanaotubes, Design of Experiments, Scanning Electron Microscopy, Maximal Electroshock Seizure, Epilepsy